Nurses’ Perceptions of the Quality of Perinatal Care Provided to Lesbian Women - Tzur-Peled, Sharona; Kushnir, Talma; Sarid, Orly (Frontiers in Psychology, 2022)
Aim: To examine whether attitudes of nurses from different ethnic groups, subjective norms, behavioural intentions, assessments of relationships and communication, are associated with their perceptions of the quality of perinatal care provided to lesbians, based on the Theory of Reasoned Action (TRA). Background: Nurses administer healthcare to lesbians from pregnancy planning through birth, providing pertinent information and consultation. Introduction: During the past few decades, worldwide, there has been a rise in lesbian-parenting. In conjunction with the changes in Israeli society's public and legal reality, intolerance and discrimination pertaining to homosexuality are still prevalent in Israel's establishment and public. Methods: This research is part of a larger cross-sectional study conducted between 12/2015-4/2016 encompassing 184 Israeli nurses who completed anonymous self-report questionnaires. Findings: Most respondents (73.4%) were acquainted with a lesbian; 64.1% agreed to provide equal care to lesbians; yet most retained negative attitudes towards lesbians (76.1%) and towards their care (83.2%). More than half (52.2%) exhibited low subjective norms related to perinatal care for lesbians. Nurses' attitudes towards lesbians, their care, subjective norms, behavioural intentions, assessment of relationships and communication significantly predicted their perceptions of the quality of perinatal care provided to lesbians. Discussion: The analysis revealed that attitudes, subjective norms, behavioural intentions, assessments of relationships and communication of nurses from different ethnic groups, were associated with their perceptions of the quality of perinatal care provided to lesbians. Conclusions: We believe that nurses will now have a better understanding of the lesbians’ status in the Israeli healthcare system. Implications for nursing and heath policy: Our findings revealed the importance of formulating a formal policy in the field of LGBT medicine at the national level.